A self-assembled ellagic acid nano-complex, and a preparation method and use thereof
Patent Information
- Application Number
- CN202410124759.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-01-30
AI Technical Summary
[0004]为了解决鞣花酸的水不溶性问题,目前尚无将自组装技术用于鞣花酸
[0031]本发明纳米复合物三种原料鞣花酸、没食子酸、表没食子儿茶素没食子酸酯EGCG,均来源于天然余甘子汁,通过反溶剂诱导法成功制备了鞣花酸复合物。该复合物的制备方法简单、成本低廉,显著提高了鞣花酸的溶解性,并大大改善了其稳定性。加入透明质酸作为凝胶基质制备复合物凝胶后,鞣花酸复合物稳定性进一步提升,同时解决了复合物液体黏性低及附着能力差的问题,有便于后续用于皮肤伤口愈合产品的开发。
Smart Images

Figure CN117959287B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a ellagic acid self-assembled nanocomposite, its preparation method and uses, and belongs to pharmaceutical preparations. Background Technology
[0002] Ellagic acid (EA) is an organic compound with the chemical formula C14H6O8. It is a polyphenolic diester and a dimer derivative of gallic acid. Ellagic acid is a natural polyphenolic component widely found in various soft fruits, nuts, and other plant tissues. It reacts with ferric chloride to produce a blue color and with sulfuric acid to produce a yellow color. Ellagic acid is a polyphenolic compound found in many fruits and nuts, such as raspberries, grapes, strawberries, pomegranates, and walnuts. Studies have shown that it has anti-proliferative and anti-apoptotic effects on certain cancer cell lines. Like other polyphenolic phytochemicals, ellagic acid also exhibits antioxidant activity in in vitro and in vivo models. In dermatology, ellagic acid is very effective in improving signs of skin aging caused by ultraviolet radiation and treating pigmentation, showing promising application prospects. Ellagic acid exists not only in its free form but also, more often, in condensed forms (such as ellagitannins and glycosides) in nature. Ellagic acid reacts with ferric chloride to produce a blue color, turns yellow with sulfuric acid, and shows a positive Greiss-Meger reaction. It also readily combines with metal cations such as Ca2+ and M. Pure ellagic acid is a yellow needle-like crystal with a melting point (pyridine) greater than 360℃. It is slightly soluble in water and alcohol, soluble in alkalis, pyridine, and dimethyl sulfoxide, and insoluble in ether. Ellagic acid possesses various biological activities, such as antioxidant, anticancer, antimutagenic properties, and inhibitory effects against human immunodeficiency virus (HIV). In addition, ellagic acid is an effective coagulant, exhibiting good inhibitory effects against various bacteria and viruses, protecting wounds from bacterial invasion, preventing infection, and inhibiting ulceration. Furthermore, studies have found that ellagic acid also has hypotensive and sedative effects.
[0003] Self-assembly is the process by which disordered molecules spontaneously arrange themselves into ordered structures (such as nanotubes, nanofibers, micelles, and vesicles) due to non-covalent forces, including hydrogen bonds, electrostatic forces, van der Waals forces, π-π interactions, hydrophobic interactions, and coordination interactions. In traditional Chinese medicine (TCM), self-assembly refers to the formation of nano-aggregates (i.e., nanoparticles) by TCM components such as amino acids, sugars, nucleoside bases, steroids, triterpenes, and coumarins through non-covalent bonds. The mechanisms of self-assembly vary among different TCM components due to their different structures. For example, the complex structure of carbohydrates is rich in hydrophilic groups, enabling them to self-assemble with other structural units through hydrophobic interactions or hydrogen bonds. Triterpenoids, on the other hand, with their rigid framework and multi-chiral centers, readily fold in various forms in different media to form self-assembled nanoparticles.
[0004] To address the issue of ellagic acid's insolubility in water, there is currently no technology that utilizes self-assembly for ellagic acid. Summary of the Invention
[0005] This invention provides an ellagic acid self-assembled nanocomposite, and also provides a method for preparing the composite and its uses.
[0006] This invention provides an ellagic acid self-assembled nanocomposite, which is prepared from ellagic acid, gallic acid, and epigallocatechin gallate (EGCG).
[0007] The molar ratio of gallic acid to EGCG is (2-10):1;
[0008] The molar ratio of ellagic acid to gallic acid is 1:(17-177).
[0009] The molar ratio of gallic acid to EGCG is 3:1; the molar ratio of ellagic acid to gallic acid is 1:133.
[0010] The present invention also provides a method for preparing the ellagic acid self-assembled nanocomposite, which includes the following steps:
[0011] a. Weigh out the raw materials ellagic acid, gallic acid, and epigallocatechin gallate (EGCG) in the specified molar proportions;
[0012] b. Preparation of ellagic acid stock solution: Ellagic acid was dissolved in N-methylpyrrolidone (NMP) to obtain ellagic acid stock solution with a concentration of 2.16-64.45 μg / mL for later use;
[0013] c. Preparation of gallic acid and EGCG aqueous solutions: Weigh gallic acid and EGCG respectively, and prepare 0.2%, 0.4%, 0.8%, 1%, 1.5% and 2% gallic acid and EGCG aqueous solutions respectively under 70℃ water bath conditions;
[0014] d. Add ellagic acid stock solution dropwise to gallic acid solution and shake well to form a binary complex. Then add an equal volume of EGCG solution and prepare the EA-GA-EGCG ternary complex by sonication, magnetic stirring, constant temperature water bath at 50-90℃ or reflux condensation, respectively.
[0015] Ellagic acid is abbreviated as EA, and gallic acid is abbreviated as GA.
[0016] More preferably,
[0017] The concentration of the gallic acid aqueous solution in step c is 1.5%;
[0018] The ultrasonic conditions described in step d are: 250W, 33kHz, 3min; the magnetic stirring conditions are: 600r / min, 70℃, 30min; the constant temperature water bath conditions are: 70℃; and the reflux time is: 30min.
[0019] The method for preparing the ternary composite in step d is a constant temperature water bath.
[0020] The present invention also provides the use of the ellagic acid self-assembled nanocomposite in the preparation of antibacterial and antimicrobial drugs.
[0021] This invention provides an ellagic acid complex gel, which is prepared by encapsulating the ellagic acid self-assembled nanocomposite in a polysaccharide matrix to form a gel.
[0022] The polysaccharide matrix is one or a mixture of two or more of the following: hyaluronic acid, quaternary ammonium chitosan, and Lota carrageenan; the amount of the matrix is 0.5-2.5% of the ellagic acid complex.
[0023] Preferably, the polysaccharide matrix is hyaluronic acid; the amount of matrix used is 1.5% of the ellagic acid complex.
[0024] The present invention also provides a method for preparing the gel, which includes the following steps:
[0025] a. Weigh out the raw materials ellagic acid, gallic acid, and epigallocatechin gallate (EGCG) in the specified molar proportions;
[0026] b. Preparation of ellagic acid stock solution: Ellagic acid was dissolved in N-methylpyrrolidone (NMP) to obtain ellagic acid stock solution with a concentration of 2.16-64.45 μg / mL for later use;
[0027] c. Preparation of gallic acid and EGCG aqueous solutions: Weigh gallic acid and EGCG respectively, and prepare 0.2%, 0.4%, 0.8%, 1%, 1.5% and 2% gallic acid and EGCG aqueous solutions respectively under 70℃ water bath conditions;
[0028] d. Add ellagic acid stock solution dropwise to gallic acid solution and shake well to form a binary complex;
[0029] e. Under constant temperature water bath conditions of 70℃, first mix the gel matrix with EGCG, then add an equal volume of the GA-EA binary complex prepared in step d, and the gel is obtained after mixing.
[0030] The present invention also provides the use of the gel in the preparation of a topical medicine for treating diabetic wounds.
[0031] The three raw materials for this invention's nanocomposite—ellagic acid, gallic acid, and epigallocatechin gallate (EGCG)—are all derived from natural amla juice. An ellagic acid complex was successfully prepared via an antisolvent-induced method. This complex preparation method is simple and inexpensive, significantly improving the solubility and stability of ellagic acid. Adding hyaluronic acid as a gel matrix further enhances the stability of the ellagic acid complex, while simultaneously addressing the issues of low liquid viscosity and poor adhesion, facilitating its subsequent development in skin wound healing products. Attached Figure Description
[0032] Figure 1 Standard curves for ellagic acid and gallic acid (Note: A: Ellagic acid standard curve; B: Gallic acid standard curve);
[0033] Figure 2 Solubilizing ability of monomers on EA (Note: A: Solubilization of EA by GA; B: Solubilization of EA by EGCG);
[0034] Figure 3 The effect of different addition sequences on the solubilizing ability of EA during the preparation of ternary complexes was investigated.
[0035] Figure 4 Investigating the solubilizing effect of different molar ratios on EA;
[0036] Figure 5 Investigation on the solubilizing ability of EA by different composite processes;
[0037] Figure 6 The effect of different water bath temperatures on the solubilizing ability of EA;
[0038] Figure 7 Stability index (TSI, top) and particle size determination results of ellagic acid complex.
[0039] Figure 8 Transmission electron microscopy images of the ternary composite
[0040] Figure 9 FTIR spectrum
[0041] Figure 10 XRD spectrum
[0042] Figure 11 1 H-NMR
[0043] Figure 12 Molecular dynamics simulation
[0044] Figure 13 In vitro antibacterial activity of each sample against Staphylococcus aureus (Note: A: diameter of inhibition zone; B: inhibition zone)
[0045] Figure 14 Screening results of polysaccharide gel materials
[0046] Figure 15 Investigation of Gel Matrix Dosage
[0047] Figure 16 Gel preparation method
[0048] Figure 17 Gel antibacterial activity
[0049] Figure 18 In vivo evaluation of ellagic acid complex gel in promoting wound healing in diabetic patients (Note: AB: wound images of different treatment groups; C: wound healing rate of different treatment groups)
[0050] Figure 19 H&E stained sections of ellagic acid complex gel treated with diabetic wounds on days 7 and 14.
[0051] Figure 20 Masson-stained sections of ellagic acid complex gel treated with diabetic wounds on days 7 and 14. Detailed Implementation
[0052] Example 1: Preparation and Condition Screening Test of Ellagic Acid Self-Assembled Complex
[0053] 1. Instruments and Materials
[0054] 1.1 Instruments
[0055]
[0056] 1.2 Materials
[0057] Ellagic acid (Sichuan Weikeqi Biotechnology Co., Ltd., batch number: wkq21010403, mass fraction ≥98%); Gallic acid (Shanghai Maclean Biotechnology Co., Ltd., batch number: C14384461, mass fraction ≥99%); Epigallocatechin gallate / EGCG (Sichuan Hengcheng Zhiyuan Biotechnology Co., Ltd.); N-methylpyrrolidone (Chengdu Kelong Chemical Co., Ltd.); Methanol (Sigma-Aldrich, USA, catalog number: WXBD7361V); Phosphoric acid (Sigma-Aldrich, USA, catalog number: WXBD2060V); Deuterated dimethyl sulfoxide (Cambridge Isotope Laboratories, Inc.); Agar (Guangzhou Shuopu Biotechnology Co., Ltd.); Brain heart extract (Qingdao High-tech Industrial Park Haibo Biotechnology Co., Ltd.).
[0058] 2. Preparation and optimization of ellagic acid self-assembled complexes
[0059] 2.1 Content determination
[0060] 2.1.1 Chromatographic conditions
[0061] Chromatographic column Welchrom C 18 Column (4.6 mm × 250 mm, 5 μm); mobile phase: 0.2% phosphoric acid aqueous solution (A) - methanol (B), gradient elution (0–6 min, 5% B; 6–15 min, 5%–7% B; 15–20 min, 7%–15% B; 20–25 min, 15%–21% B; 25–31 min, 21%–22% B; 31–41 min, 22% B; 41–47 min, 22%–28% B; 47–51 min, 28%–32% B; 51–57 min, 32%–38% B; 57–70 min, 38%–45% B; 70–80 min, 45%–65% B); detection wavelength: 270 nm; flow rate: 1.0 mL / min; column temperature: 25 °C; injection volume: 10 μL.
[0062] 2.1.2 Preparation of reference solution
[0063] Take an appropriate amount of ellagic acid reference standard, accurately weigh it, and place it in a 250 mL brown volumetric flask. Dilute to the mark with methanol, sonicate for 30 min, and cool to room temperature to obtain the reference standard stock solution. Take an appropriate amount of gallic acid reference standard, accurately weigh it, and place it in a 5 mL volumetric flask. Dilute to the mark with 50% methanol, sonicate for 30 min, and cool to room temperature to obtain the reference standard stock solution.
[0064] 2.1.3 Preparation of the test solution
[0065] After each sample was allowed to stand and cool, it was diluted with 50% methanol at an appropriate ratio, filtered through a 0.22 mm microporous membrane, and determined according to the liquid chromatography method under section 3.2.4 of Chapter 1.
[0066] 2.1.4 Standard Curve and Linear Range
[0067] Accurately pipette the reference stock solution prepared under section 2.1.2, dilute with methanol to prepare six reference solutions of different concentrations, filter each solution through a 0.22 μm microporous membrane, and then inject and determine according to the chromatographic method under section 3.4.1. Perform linear regression with peak area as the Y-axis and reference concentration as the X-axis.
[0068] 2.2 Investigation on the solubilizing ability of the self-assembled complex for ellagic acid
[0069] 2.2.1 Preparation of EA stock solution
[0070] Ellagic acid was dissolved in NMP to obtain a 1.5% ellagic acid stock solution for later use.
[0071] 2.2.2 Investigation of the solubilizing ability of EA-GA composite
[0072] Weigh out appropriate amounts of GA and prepare GA aqueous solutions of 0.2%, 0.4%, 0.8%, 1%, 1.5% and 2% respectively under a 70℃ water bath. Then add EA stock solution dropwise to the GA aqueous solutions of different concentrations, shake to mix, and filter through a 0.45μm microporous membrane.
[0073] 2.2.3 Investigation on the solubilizing ability of EA-EGCG complex
[0074] Weigh out appropriate amounts of EGCG and prepare 0.2%, 0.4%, 0.8%, 1%, 1.5% and 2% EGCG aqueous solutions respectively under 70℃ water bath conditions; then add ellagic acid stock solution dropwise to the EGCG aqueous solutions of different concentrations, shake to mix well and filter through a 0.45μm microporous membrane.
[0075] 2.2.4 Investigation on the solubilizing ability of EA-GA-EGCG composite
[0076] 3% GA and EGCG solutions were prepared separately under a 70℃ water bath for later use. The effect of different addition sequences on the ellagic acid complex was investigated. Sequence 1: Equal volumes of GA and EGCG solutions were mixed and shaken well, and then EA stock solution was added dropwise; Sequence 2: EA stock solution was added dropwise to the GA solution and shaken well, and then an equal volume of EGCG solution was added; Sequence 3: EA stock solution was added dropwise to the EGCG solution and shaken well, and then an equal volume of GA solution was added; After each sample was shaken and mixed well, it was filtered through a 0.45μm microporous membrane.
[0077] 2.3 Optimization of the preparation of EA-GA-EGCG complex
[0078] 2.3.1 Proportion of Solubilizing Substance Added
[0079] Under a 70℃ water bath, the EA stock solution was added dropwise to a 3% GA solution and shaken well; then, EGCG solutions of different concentrations were added in equal volumes, so that the molar ratio of GA to EGCG was 2:1, 3:1, 4:1, 5:1 and 10:1, respectively; after each sample was shaken and mixed, it was filtered through a 0.45μm microporous membrane.
[0080] 2.3.2 Screening of composite preparation processes
[0081] EA was added dropwise to a 3% GA solution and shaken well. Then, EGCG solutions of different concentrations were added in equal volumes to make the molar ratio of GA to EGCG 3:1. Subsequently, EA-GA-EGCG complexes were prepared by sonication (250W, 33kHz, 3min), magnetic stirring (600r / min, 70℃, 30min), constant temperature water bath (70℃), and reflux condensation (30min).
[0082] 2.3.3 Water bath temperature investigation
[0083] Prepare 3% GA and EGCG solutions at constant temperature water baths of 50, 60, 70, 80 and 90℃ respectively for later use; add EA stock solution dropwise to the GA solution and shake well, then add an equal volume of EGCG solution to make the molar ratio of GA to EGCG 3:1; after shaking well, filter each sample through a 0.45μm microporous membrane.
[0084] Characterization and antibacterial activity study of ellagic acid self-assembly system
[0085] 3.1 Stability Assessment
[0086] An aqueous solution of ellagic acid complex was poured into a multispectral sample vial to three-quarters full. Air bubbles on the surface were removed, and the vial was placed in a Turbiscan Lab stability analyzer for measurement. The scan interval was set to 30 min, for a total of 24 hours; the scan height was 50 mm; the equilibration time was 20 min; the test temperature was 25℃; the continuous phase light transmission intensity (T0) was 99.9% (water); and the dispersed phase refractive index (n) was... p The refractive index (n) is 1.36; the continuous phase refractive index (n) f The value is 1.33. The data was processed using Turbiscan Easy Sof software (version 2.2.0.82, Formulaction, France).
[0087] 3.2 Transmission Electron Microscopy
[0088] The EA-GA-EGCG complex prepared under optimal conditions was dropped onto a copper grid using a dropper. After standing for 10 minutes to dry, it was observed and photographed under a transmission electron microscope.
[0089] 3.3 Infrared Spectroscopic Analysis
[0090] Potassium bromide was ground into a fine powder in an agate mortar under an infrared lamp, then transferred to a tableting mold. The mold was pressed in a tablet press to obtain a translucent thin film, i.e., a potassium bromide blank film. Appropriate amounts of EA, GA, EGCG monomers and freeze-dried EA-GA complex, EA-GA-EGCG complex, and EA-GA-EGCG physical mixture powders were ground with potassium bromide in an agate mortar, pressed into sample films, and placed in a Fourier transform infrared spectrometer at 400-4000 cm⁻¹. -1 The one-dimensional infrared spectrum of the sample was obtained by scanning within the range.
[0091] 3.4 X-ray diffraction analysis
[0092] To verify the physical state of EA in the EA complex, X-ray diffraction analysis was performed on EA, GA, EGCG, and freeze-dried EA-GA, EA-GA-EGCG, and EA-GA-EGCG physical mixture powders. Cu-Kα was used, with a scanning range of 10°–50°, a scanning speed of 2° / min, a tube voltage of 30 kV, and a tube current of 30 mA.
[0093] 3.5H NMR
[0094] EA, GA, EGCG, and the EA-GA complex and EA-GA-EGCG complex obtained by lyophilization were dissolved in deuterated dimethyl sulfoxide, then transferred to NMR tubes and measured in an NMR spectrometer at 25°C.
[0095] 3.6 Molecular Dynamics Simulation
[0096] Theoretical calculations were performed using the Gaussian 09w program. The interaction energies of the complexes were calculated at the 6-31G(d,p) / SMD(Water) basis set level using the density functional theory M06-2X-D3 method. All structural optimizations and energy calculations were performed using Gaussian 09w software.
[0097] 3.7 Antibacterial Activity Study
[0098] 3.7.1 Bacterial Culture
[0099] Glycerol cryovials containing Staphylococcus aureus were thawed naturally in a clean bench. 10 μL of the thawed product was then transferred to HB liquid culture medium. The liquid culture medium containing the bacterial suspension was incubated at 37°C and 180 rpm for 24 hours. The bacterial suspension was then diluted with sterile water to a concentration of 1 × 10⁻⁶. 6 CFU / mL.
[0100] 3.7.2 Paper Diffusion Method
[0101] Sterilize circular filter paper discs with a diameter of 6 mm and immerse them respectively in EA-GA-EGCG complex solution, EA-GA-EGCG physical mixture, EA solution dissolved in NMP (0.2 mg / mL), and NMP; add 200 μL of Staphylococcus aureus (1×10⁻⁶) to each solution. 6 The filter paper (CFU / mL) was spread on the surface of the agar medium; after soaking for 20 minutes, the filter paper was placed on the agar plate and incubated at 37°C for 24 hours. The diameter of the inhibition zone was recorded using digital calipers.
[0102] 4 Results and Discussion
[0103] 4.1 Content determination standard curve and linear range
[0104] like Figure 1 As shown in Figure A, the regression equation for the standard curve of ellagic acid content determination is Y = 3.779X, R0 2 =1, with good linearity in the range of 14.4–36 μg / mL; Figure 1 As shown in Figure B, the regression equation for the standard curve of gallic acid content determination is Y = 3.7728X + 0.1708, R0 2 =0.9997, with good linearity in the range of 0.298–2.984 mg / mL.
[0105] 4.2 Preparation and optimization of ellagic acid self-assembled complexes
[0106] 4.2.1 Investigation on the solubilizing ability of GA and EGCG on ellagic acid
[0107] It is speculated that gallic acid may be key to the formation of the self-assembled complex and the solubilization of ellagic acid, while EGCG can initiate and promote the self-assembly of gallic acid. To investigate the solubilizing ability of gallic acid and EGCG on ellagic acid, binary self-assembled complexes of GA-EA and EGCG-EA were prepared using an antisolvent-induced method. The solubilizing ability of different concentrations of GA and EGCG on EA was investigated, and the results are as follows: Figure 2 As shown. Figure 2 The results in study A showed that when the GA concentrations were 0.2%, 0.4%, 0.8%, 1%, 1.5%, and 2%, the EA concentrations were 2.16, 6.39, 12.15, 24.69, 73.28, and 64.45 μg / mL, respectively. These results demonstrate that GA monomers can assemble and complex with EA, thus solubilizing EA, and the solubilizing ability increases with increasing GA concentration, with the strongest solubilizing ability for ellagic acid at a GA concentration of 1.5%. However, as the GA concentration continued to increase, the precipitation of GA due to cooling became more severe, which explains why the solubilizing ability for EA decreased at GA concentrations above 1.5%. Therefore, inhibiting GA precipitation is necessary to maintain the interaction between EA and GA. The solubilizing ability of different concentrations of EGCG for EA is shown in the figure below. Figure 2 As shown in Figure B, the results indicate that when the EGCG concentrations are 0.2%, 0.4%, 0.8%, 1%, 1.5%, and 2%, the EA concentrations are 1.57, 2.14, 2.52, 4.94, 12.39, and 10.18 μg / mL, respectively. It can be observed that the direct solubilizing ability of EGCG monomer for EA is very weak, indicating that stable assembly between EGCG monomer and EA is difficult to achieve directly.
[0108] 4.2.2 Investigation on the solubilization of ellagic acid by the EA-GA-EGCG self-assembled complex
[0109] The above results indicate that GA and EA can form a self-assembled complex, but its stability is limited, and EGCG cannot directly assemble with EA. Therefore, in preparing the ternary self-assembled complex, the effect of different compounding orders of the three components on the complex formation was investigated and compared. The solubilizing concentration of ellagic acid for preparing the EA-GA-EGCG complex with different addition orders is as follows: Figure 3 As shown in the figure. The results indicate that when GA and EGCG solutions were mixed first and then EA was added dropwise, the concentration of EA was 82.28 μg / mL; when EA was added dropwise to the EGCG solution first and then an equal volume of GA solution was mixed, the concentration of EA was 48.27 μg / mL; and when EA was added dropwise to the GA solution first and then an equal volume of EGCG solution was mixed, the concentration of EA was 122.32 μg / mL. Together with the results in 4.2.1 above, this indicates that in the ellagic acid self-assembly system, the first step of assembly was achieved between GA and EA, followed by the second step of assembly between the subsequently added EGCG and the GA-EA complex. Therefore, the optimal assembly order is to first form a binary complex between GA and EA, and then add EGCG to form a ternary complex.
[0110] 4.2.3 Proportion of Solubilizing Substances Added
[0111] When preparing ternary complexes using different GA to EGCG molar ratios, the solubilizing concentration of EA is as follows: Figure 4 As shown in the figure. The results indicate that when the molar ratios of GA to EGCG were 2:1, 3:1, 4:1, 5:1, and 10:1, the concentrations of EA were 39.36, 202.94, 122.23, 47.05, and 37.82 μg / mL, respectively. It can be found that a molar ratio of GA to EGCG of 3:1 maximally solubilizes EA.
[0112] 4.2.4 Screening of composite preparation processes
[0113] When preparing the EA-GA-EGCG complex using different complex preparation processes, the solubilization concentration of EA is as follows: Figure 5 As shown in the figure. The results indicate that when preparing the EA-GA-EGCG complex under ultrasonic, magnetic stirring, constant temperature water bath, and reflux conditions, the concentrations of EA were 55.95, 38.92, 202.94, and 43.93 μg / mL, respectively, with the constant temperature water bath being the optimal process.
[0114] 4.2.5 Investigation of water bath temperature for composite preparation
[0115] When preparing the EA-GA-EGCG complex at different water bath temperatures, the solubilizing concentration of EA is as follows: Figure 6As shown in the figure. The results indicate that when the EA-GA-EGCG complex was prepared at 50, 60, 70, 80 and 90 °C, the concentrations of EA were 78.68, 89.76, 202.94, 167.62 and 50.08 μg / mL, respectively.
[0116] 4.3 Characterization of ellagic acid complex
[0117] 4.3.1 Stability and particle size results
[0118] Multiplex optical emission analysis of the ellagic acid complex showed that the TSI index stabilized after 4 hours, remaining around 3, lower than the TSI index of ellagic acid monomer in aqueous solution. This indicates that the ellagic acid complex effectively solubilizes and stabilizes ellagic acid. Particle size analysis showed some fluctuations in the early stages of dissolution, possibly related to the dissolution process. The particle size of the ellagic acid complex stabilized after 4 hours, remaining around 150 nm. All these results demonstrate that the complex effectively stabilizes ellagic acid molecules, and the particle size of the complex is approximately 150 nm. Figure 7 ).
[0119] 4.3.2 Transmission Electron Microscopy
[0120] Transmission electron microscopy (TEM) can observe the microstructure of self-assembled complexes in solution, and the results help in inferring the interactions between components. For example... Figure 8 As shown, the ellagic acid complex exhibits a relatively regular layered stacked rod-like structure, with lengths of approximately 300–500 nm, and some parts appearing as spherical shapes with a diameter of approximately 100 nm. According to the literature "Self-Assembly of Naturally Small Molecules into Supramolecular Fibrillar Networks for Wound Healing," GA can form a layered stacked rod-like structure through π-π stacking and hydrogen bonding interactions. Considering the order in which the substances were added during the preparation of the ellagic acid complex, it can be inferred that the rod-like main body in the figure is formed by the stacking of GA, with EA embedded within its layered structure. EGCG was added last and may exist on the outer layer of the rod-like main body, binding to GA through hydrogen bonds, effectively stabilizing the stacked structure of GA.
[0121] 4.4 Study on the self-assembly mechanism of the complex
[0122] 4.4.1 Infrared Spectrum
[0123] When non-covalent interactions exist between or within molecules, the shifts or intensities of the corresponding vibrational absorption peaks in the infrared spectrum will exhibit regular changes. Figure 9 The image shows the infrared spectra of each sample. In the FTIR spectrum of EA, 3477 cm⁻¹-1 The peak at 1720 cm⁻¹ is the stretching vibration peak of -OH. -1 The strong absorption peak at 1449-1620 cm⁻¹ is due to the stretching vibration of the carbonyl group on the ester bond. -1 The absorption peaks within this range are characteristic absorption peaks of the aromatic ring skeleton. In the FTIR spectrum of GA, 3495 cm⁻¹ is a characteristic peak. -1 The peak at 1666 cm⁻¹ is the stretching vibration peak of -OH. -1 The peak at 3480 cm⁻¹ represents the stretching vibration of the carbonyl group. In the FTIR spectrum of EGCG, this peak is located at 3480 cm⁻¹. -1 The peak at 1690 cm⁻¹ is the stretching vibration peak of -OH. -1 The peak at 3558 cm⁻¹ represents the stretching vibration of the carbonyl group. In the FTIR spectrum of a physical mixture of the three components, the peaks are located at 3558 cm⁻¹. -1 3495cm -1 3356cm -1 and 3382cm -1 Characteristic absorption peaks of EGCG, GA, and EA were observed, indicating that the physical mixture is a simple mixture of monomers without any interactions. In the spectrum corresponding to the EA-GA complex, the absorption peak of -OH shifted significantly to a lower wavenumber, reaching 3391 cm⁻¹. -1 Furthermore, the broad peak shape indicates that intermolecular hydrogen bonds have formed between the hydroxyl groups of EA and GA; in addition, at 1695 cm⁻¹... -1 A strong absorption peak belonging to the carbonyl group was observed, suggesting that intermolecular hydrogen bonds formed between the -COOH groups in GA, leading to association between the carbonyl groups on the -COOH group and the formation of the GA dimer. In the spectrum corresponding to the EA-GA-EGCG complex, the stretching vibration peak of -OH further shifted significantly to lower wavenumbers, reaching 3202 cm⁻¹. -1 A very broad and blunt vibrational absorption peak appears at 1694 cm⁻¹, indicating that a large number of hydrogen bonds have formed between the hydroxyl groups of the three components; -1 The carbonyl vibration absorption peak still appeared at 1695 cm⁻¹, similar to that in the EA-GA complex. -1 Compared to the absence of significant displacement, this indicates that GA retains its dimer structure after the addition of EGCG, with the increase in hydrogen bonds being the main change.
[0124] 4.4.2 X-ray diffraction analysis
[0125] Generally, hydrophobic bioactive substances are released more effectively from amorphous particles than from crystalline particles. Therefore, we used XRD patterns to assess the physical state of EA in the complex. XRD patterns for all samples are shown below. Figure 10As shown, powdered EA, being a crystal, exhibits multiple distinct diffraction peaks in the 2θ range of 12.2–28.2° (12.2, 13.5, 13.9, 17.4, 20.9, 23.8, 25.1, 26.2, and 28.2). Similarly, GA and EGCG monomers, also crystalline, display numerous diffraction peaks. It is readily observed that the diffraction peaks of the EA-GA and EA-GA-EGCG complexes are significantly reduced and weakened. This indicates that the interactions between the monomers suppress their respective crystallization tendencies, which not only explains the substantial increase in EA solubility but also, to some extent, the slight increase in the solubility of GA and EGCG. However, several distinct diffraction peaks still remain in the complex's spectrum, due to the persistent presence of uninteracted, free crystalline monomers within the complex.
[0126] 4.4.3H 1 1H NMR spectrum
[0127] To further explore the formation mechanism of ellagic acid complexes, this study compared the formation process of self-assembled complexes. 1 Changes in the 1H NMR spectrum Figure 11 For each sample 1 H-NMR spectrum. In GA 1 In the 1H-NMR spectrum, from low field to high field, the absorption peaks are: 12.22 ppm for the carboxyl hydrogen, 9.18 ppm for the meta-phenolic hydroxyl hydrogen, 8.82 ppm for the para-phenolic hydroxyl hydrogen, and 6.91 ppm for the hydrogen on the benzene ring. The shift values of the carboxyl hydrogen in GA are in the range of 10-13 ppm, indicating that the carboxyl groups exist in a dimer form and form bimolecular hydrogen bonds. This suggests that the two GA molecules in the layered stacked structure are stacked as a single unit. After the formation of the EA-GA binary complex, the carboxyl hydrogen peak of GA becomes increasingly sharp, indicating that compared to the GA monomer, some carboxyl groups in GA may form hydrogen bonds with the hydroxyl groups in the EA structure, thus weakening the hydrogen bonds between GA carboxyl groups. When the EA-GA-EGCG ternary complex is formed, the peak shape changes to a broad peak, and the exchange rate of GA carboxyl hydrogen slows down. This suggests that the addition of EGCG weakens the hydrogen bond between EA and GA and further enhances the self-assembly force between GA molecules. In EA... 1In the 1H-NMR spectrum, 10.69 ppm represents the absorption peak of the four phenolic hydroxyl hydrogens, and 7.46 ppm represents the absorption peak of the hydrogens on the benzene ring. When EA forms the EA-GA binary complex, the singlet at 10.69 ppm splits into a symmetrical doublet, indicating that intermolecular hydrogen bonds have formed between the phenolic hydroxyl groups of EA and GA, causing coupling between hydrogens on adjacent phenolic hydroxyl groups of EA, resulting in peak splitting. When EA-GA further forms the EA-GA-EGCG ternary complex, this doublet shifts synchronously to a lower field, indicating that hydrogen bonds may also have formed between EA and EGCG molecules, increasing the number of hydrogen bonds.
[0128] 4.4.4 Molecular Dynamics Simulation
[0129] Based on the above characterization and spectral analysis results, the study used Gaussian simulations to predict the self-assembly binding sites and interaction modes between molecules, and calculated the Gibbs free energy change (ΔG) during molecular assembly, in order to more clearly explain the formation mechanism of the ellagic acid ternary complex and explain the solubilization phenomenon of ellagic acid. Figure 12 As shown, GA molecules can form a planar dimer structure through hydrogen bonds formed by carboxyl groups, and then form a stacked layered structure by π-π stacking interactions, which is consistent with the above prediction. EA molecules contain a four-membered ring and are typical planar structures. When EA is added to GA, EA can embed into the gaps in the planar layered structure formed by GA and bind to GA through hydrogen bonds and π-π interactions. The Gibbs free energy of this process is -13.7 kcal / mol, indicating that the assembly of GA and EA is spontaneous and has a strong reaction tendency. EGCG has a non-planar structure and contains multiple active hydrogens. When EGCG is added to the EA-GA binary complex, EGCG can form hydrogen bonds with the adjacent GA layers, thus "encapsulating" the EA molecules in the three-dimensional space they form. The Gibbs free energy of this process is -4.9 kcal / mol, also spontaneous, but the reaction tendency is not as strong as that of GA-EA. It is speculated that, apart from EGCG, one or more other chemical components that can simultaneously form hydrogen bonds with adjacent GA interlayers can replace EGCG in the preparation of ellagic acid ternary complexes.
[0130] 4.5 In vitro antibacterial activity of ellagic acid complex
[0131] To investigate whether ellagic acid complexes possess stronger in vitro antibacterial activity, the antibacterial activities of ellagic acid monomers, EA-GA-EGCG mixtures, and EA-GA-EGCG complexes were compared. Staphylococcus aureus, a very common skin infection bacterium, was selected for the experiment. The results are as follows: Figure 13As shown, ellagic acid monomer dissolved in NMP showed almost no antibacterial activity, with an inhibition zone diameter of 6.3 ± 0.24 mm, and the solvent NMP itself had no antibacterial activity. The inhibition zone diameter of the physical mixture was 12.5 ± 0.71 mm. The ellagic acid complex exhibited the strongest antibacterial activity, with an inhibition zone diameter of 16 ± 0.63 mm. The physical mixture inhibited the growth of Staphylococcus aureus, mainly due to the antibacterial abilities of GA and EGCG dissolved in the solution. When EA formed a self-assembled complex with GA and EGCG, it showed stronger antibacterial activity than both the dissolved EA monomer and the physical mixture. This suggests that after solubilizing EA, they may be able to continuously deliver EA to bind to bacteria, and that the components can exert a certain synergistic antibacterial effect, thereby more efficiently inactivating bacteria.
[0132] Example 2: Preparation of the complex and gel of the present invention
[0133] Complex preparation process: Ellagic acid was dissolved in N-methylpyrrolidone to obtain a 15 mg / mL ellagic acid stock solution; 150 mg gallic acid was weighed and added to 5 mL of water, and dissolved in a 70 °C water bath. Then, 134 μL of ellagic acid stock solution was added dropwise while hot, which is solution A; 135 mg EGCG was weighed and added to 5 mL of water, and dissolved in a 70 °C water bath, which is solution B; solutions A and B were mixed while hot to obtain the complex solution.
[0134] Preparation process of the complex gel: Ellagic acid was dissolved in N-methylpyrrolidone to obtain a 15 mg / mL ellagic acid stock solution; 150 mg gallic acid was weighed and added to 5 mL of water, and dissolved in a 70 °C water bath. Then, while hot, 134 μL of the ellagic acid stock solution was added dropwise, which is solution A; 135 mg EGCG was weighed and added to 5 mL of water, and dissolved in a 70 °C water bath. Then, 150 mg hyaluronic acid was added and thoroughly dissolved and mixed on a magnetic stirrer to obtain gel C; solution A and gel C were mixed to obtain the complex gel.
[0135] Example 3: Preparation of Ellagic Acid Complex Gel Dressing
[0136] 1. Instruments and Reagents
[0137] 1.1 Instruments
[0138]
[0139] 1.2 Reagents
[0140] Hyaluronic acid (Shanghai Yuanye Biotechnology Co., Ltd., batch number: J31IS206158); Ellagic acid (Sichuan Weikeqi Biotechnology Co., Ltd., batch number: wkq21010403, mass fraction ≥98%); Gallic acid (Shanghai Maclean Biotechnology Co., Ltd., batch number: C14384461, mass fraction ≥99%); Epigallocatechin gallate / EGCG (Sichuan Hengcheng Zhiyuan Biotechnology Co., Ltd.); N-methylpyrrolidone (Chengdu Kelong Chemical Co., Ltd.); Methanol (Sigma-Aldrich, USA, catalog number: WXBD7361V); Phosphoric acid (Sigma-Aldrich, USA, catalog number: WXBD2060V); Agar (Guangzhou Shuopu Biotechnology Co., Ltd.); Brain heart extract (Qingdao High-tech Industrial Park Haibo Biotechnology Co., Ltd.).
[0141] 2. Preparation of Ellagic Acid Complex Hydrogel Dressing
[0142] 2.1 Screening of Gel Matrix Types
[0143] Under constant temperature water bath conditions of 70℃, 1.5% of polysaccharide-based gelling materials (hyaluronic acid, quaternary ammonium chitosan, and Lota carrageenan) were added to the prepared ellagic acid complex and stirred until homogeneous. Each sample was diluted with 50% methanol and filtered through a 0.45 μm microporous membrane to determine the concentration of EA to evaluate the stabilizing effect of different gelling materials on the complex.
[0144] 2.2 Investigation on the amount of gel matrix used
[0145] Under constant temperature water bath conditions of 70℃, 0.5%, 1%, 1.5%, 2%, and 2.5% gel material were added to the prepared ternary composite and stirred until homogeneous. Each sample was diluted with 50% methanol and filtered through a 0.45 μm microporous membrane to determine the concentration of EA to evaluate the effect of different gel matrix amounts on the stability of the composite.
[0146] 2.3 Investigation of Gel Preparation Methods
[0147] Ellagic acid complex gels were prepared using the following three methods: ① The gel material was directly added to the prepared ellagic acid complex and stirred until homogeneous; ② Under a constant temperature water bath at 70℃, the gel material was first mixed with EGCG, and then an equal volume of GA-EA binary complex was added and stirred until homogeneous; ③ Under a constant temperature water bath at 70℃, the gel material, EGCG, and GA were first mixed, and then EA was added dropwise and stirred until homogeneous.
[0148] Characterization of 3-ellagic acid complex hydrogel
[0149] 3.1 Study on the in vitro release behavior of ellagic acid in gel
[0150] Two mL of hydrogel was immersed in a test tube containing 10 mL of PBS, and the tube was placed in a shaker at 37°C. The liquid was removed at specific time points, and an equal volume of PBS was added to the release system. EA release was measured over 48 hours. A standard curve of absorbance at 289 nm and EA solubility was used to determine EA release from the hydrogel. Zero-order, first-order, Higuchi, and Ritger-Peppas models were used to analyze the EA release mechanism in the hydrogel.
[0151] 3.2 Particle size and PDI
[0152] The gel was diluted 10 times with distilled water, and its particle size and PDI were determined. Each sample was repeated 3 times.
[0153] 3.3 Hardness, brittleness, adhesion and elasticity
[0154] First, the hydrogel was prepared into cylindrical samples (14 mm in diameter and 3 mm in height) at room temperature. Then, full texture profile analysis (TPA) was performed using a rapid TA+ (Shanghai Tengbo instrument). The experiment used an X probe, with a pre-test rate of X mm / s, a test rate of X mm / s, a post-test rate of X mm / s, a compression percentage of X%, a residence time of 5 s, and a trigger force of X g. Each sample was tested three times.
[0155] Aladdin > 1.8 285.3 285.3 -1724.877 0.817 307.5 257.9 -1800.472 0.826 300.1 300.1 -1764.319 0.822 mean 297.6 281.1 -1763.222667 0.821667 Standard deviation 11.3 21.41121 37.80942298 0.004509
[0156] 3.4 Gel Rheological Properties
[0157] The rheological properties of the composite gel were evaluated using a rheometer. Linear viscoelasticity was measured at XX% strain and a fixed angular frequency of X Hz. Shear viscosity ranged from 0.1 to 1000 s⁻¹. -1 The shearing rate was [value].
[0158] 4 Results and Discussion
[0159] 4.1 Investigation of gel preparation methods
[0160] 4.1.1 Gel matrix screening
[0161] The study compared the stabilizing effects of three polysaccharide gel materials on the complex, and the results are as follows: Figure 14 As shown, with a fixed amount of matrix material, the gel prepared with hyaluronic acid has the best stabilizing effect on the complex. Therefore, hyaluronic acid was chosen as the gel matrix for subsequent gel preparation.
[0162] 4.1.2 Investigation on the amount of gel matrix used
[0163] Based on the selection of hyaluronic acid as the gel matrix, ellagic acid complex gels were prepared with hyaluronic acid contents of 0.5%, 1%, 1.5%, 2%, and 2.5%, respectively. The drug loading of the prepared gels is shown in [reference needed]. Figure 15 When the hyaluronic acid content is 1.5%, the prepared gel has the strongest stabilizing effect on the ellagic acid complex and can encapsulate the largest amount of ellagic acid. Therefore, the final matrix amount of the gel was chosen to be 1.5%.
[0164] 4.1.3 Investigation of Gel Preparation Methods
[0165] The study compared three methods for preparing ellagic acid complex gels, and the results are as follows: Figure 16 As shown, the results indicate that the gel prepared by first mixing the gel material with EGCG and then adding an equal volume of GA-EA binary complex under a constant temperature water bath at 70℃ is the clearest and can encapsulate about 200 μg / mL of ellagic acid. This method can be used as the preparation method for the gel.
[0166] The following efficacy tests demonstrate the beneficial effects of this invention.
[0167] Experimental Example 1: Pharmacodynamic study of the gel of the present invention used in diabetic wounds
[0168] 1. Instruments and Materials
[0169] 1.1 Instruments
[0170]
[0171] 1.2 Materials
[0172] Ellagic acid (Sichuan Weikeqi Biotechnology Co., Ltd., batch number: wkq21010403, mass fraction ≥98%); Gallic acid (Shanghai Maclean Biotechnology Co., Ltd., batch number: C14384461, mass fraction ≥99%); EGCG (Sichuan Hengcheng Zhiyuan Biotechnology Co., Ltd.); Hyaluronic acid (Haiyuanye Biotechnology Co., Ltd., batch number: J31IS206158); Agar (Guangzhou Shuopu Biotechnology Co., Ltd.); Brain heart extract (Qingdao High-tech Industrial Park Haibo Biotechnology Co., Ltd.); N-methylpyrrolidone (Chengdu Kelong Chemical Co., Ltd.); Anhydrous ethanol (Sinopharm Chemical Reagent Co., Ltd.).
[0173] 1.3 Animals
[0174] 16 SPF-grade male SD rats, weighing 150g-180g, were purchased from Beijing Sibeifu Biotechnology Co., Ltd. (Production License No.: SCXK (Beijing) 2019-0010). All rats were housed in a standard animal feeding room at a temperature of 20-25°C, a humidity of 40%-70%, and a 12-hour day-night alternating light cycle. This study was reviewed and approved by the Ethics Committee of Chengdu University of Traditional Chinese Medicine.
[0175] 2 Evaluation of the antibacterial activity of the gel
[0176] 2.1 Bacterial culture
[0177] Same as the section under 13.7.1 in the Example.
[0178] 2.2 Cup-plate method
[0179] Three sterilized Oxford cups were dispersedly placed on the surface of each medium coated with 200 μL of Staphylococcus aureus (1×10 6 CFU / mL) bacterial solution, and gently pressed to make them contact with the medium without gaps. Subsequently, ellagic acid gel, mixture gel and composite gel were added into the Oxford cups respectively. After the medium was incubated at 37°C for 24 hours, the diameter of the inhibition zone was recorded using a digital caliper.
[0180] 3 Wound repair effect of the gel
[0181] 3.1 Model establishment and drug administration
[0182] Before modeling, all rats were adaptively fed for 3 days in the feeding environment, and then fed with high-fat diet for three weeks. After three weeks of feeding, the rats were fasted for 12 hours and then weighed. 1% STZ (prepared with sodium citrate buffer in the dark) was intraperitoneally injected into the rats at a dose of 35 mg / kg to destroy the islet β cells of the rats. After continuing to feed with high-fat diet for three days, blood was collected from the tail vein to measure the blood glucose of the rats, and rats with a blood glucose value greater than 16.8 mmol / L were regarded as hyperglycemic rats. The rats in the control group were fed normally. All rats were anesthetized with 20% urethane, the hair on the back was removed and then disinfected with 75% alcohol, and then a skin punch was used to make two 8 mm round holes on the back of each rat. 4 healthy rats and 16 hyperglycemic rats were divided into a control group (healthy rats, no drug administration), a model group (hyperglycemic rats, no drug administration), an EA gel group (hyperglycemic rats, ellagic acid gel), a Phm gel group (hyperglycemic rats, physical mixture gel) and a Com gel group (hyperglycemic rats, ellagic acid composite gel), with 4 rats in each group. All treatments were performed once a day for 14 consecutive days.
[0183] 3.2 Macroscopic analysis and histopathological analysis
[0184] Wound area was recorded on days 0, 2, 6, 10, and 14 post-traumatic injury. Wound healing rate (%) was calculated as (C0 - C1) / C0 × 100% (where C0 is the initial area and C1 is the measured area). Furthermore, to further observe skin regeneration and collagen deposition, rats were sacrificed on days 7 and 14, and skin samples from the wound and surrounding area were collected and immersed in 10% formalin. Hematoxylin-eosin (H&E) staining and Masson staining were performed on the skin tissue according to standard procedures.
[0185] 4 Results and Discussion
[0186] 4.1 Antibacterial activity of the gel, see Figure 17 .
[0187] 4.2 Wound healing effect in diabetic rats
[0188] Wound healing status of diabetic rats in each group as follows Figure 18 As shown in Figures AB, the results revealed that the EAgel and Mix gel groups, similar to the model group, exhibited slow healing within 6 days, with redness and swelling around the wound in the early healing stage, presumably due to wound infection. This indicates that undissolved EA and its physical mixture with GA and EGCG did not improve the difficulty in wound healing in diabetic rats. In contrast, the control and Comgel groups showed significantly better early healing than the other three groups, with clear and smooth wound edges, indicating that molecularly present EA can significantly improve the difficulty in wound healing caused by inflammation and other factors in the early stages of diabetic rat wound healing. During days 7-14, healing was relatively rapid in all groups, generally consistent with the healing characteristics of diabetic rat wounds, which are difficult to heal in the early stages but tend to normalize in the later stages. On the final day, day 14, the Com gel group showed the smallest wound area, while the model group had the largest wound, with surrounding skin damage, indicating the worst healing effect. Figure 18 Figure C shows the wound healing rate of rats in each group. The results showed that there was no significant difference between the PE gel group and the Mixgel group. The healing rate was slightly higher than that of the model group but lower than that of the control group, which is presumably due to the hyaluronic acid matrix in the formulation playing a certain role in promoting healing. Ellagic acid present in the molecular state in Com gel can significantly improve the difficulty of wound healing in the early stage of diabetes and accelerate wound contraction and closure, resulting in a significantly higher healing rate than that of the control group.
[0189] 4.3 H&E staining analysis of wound
[0190] A complete skin consists of three parts: the epidermis, the dermis, and the subcutaneous tissue. For example... Figure 19As shown, seven days after wound healing in diabetic rats, the Model group, PE gel group, and Mixgel group showed low epidermal structural integrity and varying degrees of bulging, with obvious inflammation and swelling at the wound site. The EAgel group and Mixgel group showed no significant difference. All three groups had a large amount of immature granulation tissue under the skin, but the degree was slightly less than that in the model group. The control group and Com gel group had the most intact epidermis, especially the Com gel group, whose epidermis was continuous and smooth, indicating the best recovery. In these two groups, intact skin appendages, including sebaceous glands and hair follicles, were visible on both sides of the immature granulation tissue under the skin, indicating good subcutaneous recovery. Fourteen days after wound healing, the epidermis in all groups was relatively intact, with neatly arranged tissue and skin appendages tending towards completeness. Among them, the Com gel group had the smoothest and flattest epidermis, indicating the best wound recovery. The injectable self-healing adhesive chitosan hydrogel has antioxidant, antibacterial, and hemostatic activities, enabling rapid hemostasis and skin wound healing.
[0191] 4.4 Masson staining analysis of the wound
[0192] like Figure 20 As shown, seven days after wound healing in diabetic rats, the collagen deposition in the control group and the Com gel group was significantly higher than that in the model group, the EA gel group, and the Mixgel group. Among them, the collagen fiber density in the Com gel group was significantly stronger than that in the control group, demonstrating the strongest skin regeneration capacity. After 14 days of healing, all groups showed relatively dense collagen deposition and tight arrangement. In particular, the collagen production in the dermal region of the Com gel group and the Control group was higher than that of other groups, and the collagen deposition was more obvious, indicating that the ellagic acid complex can more effectively promote collagen production at the wound site.
Claims
1. A self-assembled ellagic acid nanocomposite, characterized in that: It is prepared from ellagic acid, gallic acid, and epigallocatechin gallate, among which... The molar ratio of gallic acid to epigallocatechin gallate is 3:1; the molar ratio of ellagic acid to gallic acid is 1:
133. The preparation method of the complex includes the following steps: a. Weigh out the raw materials ellagic acid, gallic acid, and epigallocatechin gallate in each molar ratio; b. Preparation of ellagic acid stock solution: Ellagic acid is dissolved in N-methylpyrrolidone to obtain an ellagic acid stock solution with a concentration of 1.5% for later use; c. Preparation of aqueous solutions of gallic acid and epigallocatechin gallate: Weigh gallic acid and epigallocatechin gallate separately, and prepare aqueous solutions of gallic acid and epigallocatechin gallate of 0.2%, 0.4%, 0.8%, 1%, 1.5% and 2% respectively under 70℃ water bath conditions. d. Add ellagic acid stock solution dropwise to gallic acid aqueous solution and shake well to form a binary complex. Then add an equal volume of epigallocatechin gallate aqueous solution and heat in a constant temperature water bath at 50-90℃ to prepare an ellagic acid-gallic acid-epigallocatechin gallate ternary complex.
2. A method for preparing the ellagic acid self-assembled nanocomposite according to claim 1, characterized in that: It includes the following steps: a. Weigh out the raw materials ellagic acid, gallic acid, and epigallocatechin gallate in each molar ratio; b. Preparation of ellagic acid stock solution: Ellagic acid is dissolved in N-methylpyrrolidone to obtain an ellagic acid stock solution with a concentration of 1.5% for later use; c. Preparation of aqueous solutions of gallic acid and epigallocatechin gallate: Weigh gallic acid and epigallocatechin gallate separately, and prepare aqueous solutions of gallic acid and epigallocatechin gallate of 0.2%, 0.4%, 0.8%, 1%, 1.5% and 2% respectively under 70℃ water bath conditions. d. Add ellagic acid stock solution dropwise to gallic acid aqueous solution and shake well to form a binary complex. Then add an equal volume of epigallocatechin gallate aqueous solution and heat in a constant temperature water bath at 50-90℃ to prepare an ellagic acid-gallic acid-epigallocatechin gallate ternary complex.
3. The method for preparing the ellagic acid self-assembled nanocomposite according to claim 2, characterized in that: The concentration of the gallic acid aqueous solution in step c is 1.5%; The constant temperature water bath conditions described in step d are 70℃.
4. The use of the ellagic acid self-assembled nanocomposite according to claim 1 in the preparation of antibacterial drugs; wherein the bacteria is Staphylococcus aureus.
5. An ellagic acid complex gel, characterized in that: It is prepared by encapsulating the ellagic acid self-assembled nanocomposite of claim 1 in a polysaccharide matrix to form a gel; The polysaccharide matrix is hyaluronic acid; the amount of the matrix used is 0.5-2.5% of the ellagic acid complex.
6. The ellagic acid complex gel according to claim 5, characterized in that: The amount of matrix used is 1.5% of the ellagic acid complex.
7. A method for preparing the gel according to claim 5 or 6, characterized in that: It includes the following steps: a. Weigh out the raw materials ellagic acid, gallic acid, and epigallocatechin gallate in each molar ratio; b. Preparation of ellagic acid stock solution: Ellagic acid is dissolved in N-methylpyrrolidone to obtain an ellagic acid stock solution with a concentration of 1.5% for later use; c. Preparation of aqueous solutions of gallic acid and epigallocatechin gallate: Weigh gallic acid and epigallocatechin gallate separately, and prepare aqueous solutions of gallic acid and epigallocatechin gallate of 0.2%, 0.4%, 0.8%, 1%, 1.5% and 2% respectively under 70℃ water bath conditions. d. Add ellagic acid stock solution dropwise to gallic acid solution and shake well to form a binary complex; e. Under constant temperature water bath conditions of 70℃, first mix the gel matrix with epigallocatechin gallate, then add an equal volume of the gallic acid-ellagic acid binary complex prepared in step d, and the gel is obtained after mixing.
8. Use of the gel according to claim 5 or 6 in the preparation of a topical medicament for treating diabetic wounds.